(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
The aim of the study: to achieve bone union and restore the function of the affected limb after controlling the infection as soon as possible and at the lowest possible financial cost. METHODOLOGY AND MATERIALS: A comprehensive study was conducted for each patient case separately, then all patients were subjected to treatment according to two surgical stages. The first stage includes a wide surgical debridement with removal of the internal fixatores and fixation with an external fixator AO with the implantation of the continuous antibiotic perfusion system for all patients, the second stage includes a procedure Bone grafting with autologous bone grafting in all patients Patients were followed up for a year with periodic clinical, laboratory and radiological evaluation. Results: The total sample amounted to 29 patients with an average age of 39.5 years, 22 males, 7 females, distribution of patients according to the place of injury 13 tibia 8 femur 5 humerus 2 radius 1 ulna, the average number of previous surgeries was 1.9 operations, the infection was controlled after the first stage In 27 patients by 92%, while the septic activity persisted in two patients by 8%, 27 patients underwent the second stage, bone fracture union was achieved in 25 patients with a percentage of 92.5% and vaccination failure in two patients by 7.5%, the average duration of treatment was 249 days. Conclusion: The process of controlling infection is the key to the success of all procedures and therapeutic measures that are performed to compensate for bone defect in patients with osteomyelitis.